Iraq and the case for Australian war crimes trials - Doran, Chris (Crime, law and social change, 2011)
This article presents the case for Australian war crimes trials, following Australian participation in the invasion of Iraq and the subsequent deaths of as many as a million Iraqi civilians. It focuses on jus in bello (war crimes) rather than jus ad bellum (just war). The article sets out the argument and rationale that Australian war crimes trials are needed. Having established the necessity, the article identifies two of the principal alleged atrocities for which Australian officials should be held criminally accountable. It details Australian military support for the use of cluster bombs against civilians during the 2003 invasion, and senior Australian military commanders’ responsibility for planning and carrying out multiple purported war crimes during the attack on Fallujah in late 2004. The article recognises that, in order for Australian officials to be prosecuted under the International Criminal Court (ICC), all domestic remedies must be first exhausted. It therefore specifically addresses which Australian laws can be used, with particular emphasis on anti-terrorist legislation passed in 2002 under the Howard Government and the introduction into Australia’s domestic federal criminal legislation offences equivalent to the ICC Statute offences of genocide, crimes against humanity and war crimes. These provide the most applicable legal tools for prosecuting senior Australian officials for war crimes in Iraq.